PERANCANGAN KANTOR DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KOTA BANJARBARU DENGAN PENERAPAN ARSITEKTUR KOLONIAL MODERN - Sopha, Rizky Naila; Anhar, Pakhri (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
The Banjarbaru City Public Works and Spatial Planning Office is one of the official offices located in the Murjani area. This design was carried out because of functional considerations that did not meet the capacity and the Murjani area had a high value in post-independence architecture. The purpose of this design is how to design a representative office according to the needs of its activities and can strengthen the reflection of the Murjani area which has a high value on post-independence architecture. In this design, two methods are used, namely programmatic and historical methods. In this method, the concept of colonial architecture is obtained. This concept is used to reflect the Murjani area which has a high value in colonial architecture. It is hoped that these two methods can produce an appropriate design.